A suitor for Jenny [large type] - Brownley, Margaret (Thorndike Press large print Christian romance, 2010)
When looking for a husband, it's best to go where the odds are in your favor. And that would be Rocky Creek, Texas, 1880. Jenny Higgins' plan to find husbands for her two sisters hits a snag when enthusiastic applicants fail to meet her stringent requirements. Rejecting her sisters' choices for mates and riding herd on her growing feelings for Marshal Rhett Armstrong, she refuses to give up. Jenny thinks choosing a husband is not a job for the heart. One strong, handsome marshal may convince her otherwise.